2007
DOI: 10.1002/ajmg.a.31597
|View full text |Cite
|
Sign up to set email alerts
|

KBG syndrome: Report of twins, neurological characteristics, and delineation of diagnostic criteria

Abstract: KBG syndrome is a multiple congenital anomaly (MCA) syndrome comprising developmental delay, postnatal short stature, and delayed bone age. Many physical anomalies involving the face, hands, and costovertebral axis have been described in this syndrome. We present twin males with KBG syndrome and a review of 50 published case reports, with particular emphasis on the neurological aspects of KBG syndrome, including seizures, MRI findings, and behavior difficulties. It is argued that diagnostic criteria for KBG sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(135 citation statements)
references
References 10 publications
3
132
0
Order By: Relevance
“…Until recently, the clinical diagnosis of KBG syndrome has been based on criteria described by Skjei et al [4]. Postnatal short stature, defined as height below centile 3 (-1.88 SDS) with a birth weight above centile 3 is one of these criteria.…”
Section: Literature Review Of Height In Kbg Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, the clinical diagnosis of KBG syndrome has been based on criteria described by Skjei et al [4]. Postnatal short stature, defined as height below centile 3 (-1.88 SDS) with a birth weight above centile 3 is one of these criteria.…”
Section: Literature Review Of Height In Kbg Syndromementioning
confidence: 99%
“…Postnatal short stature, defined as height below centile 3 (-1.88 SDS) with a birth weight above centile 3 is one of these criteria. In the report of Skjei et al [4], 46 clinically diagnosed patients were described: 83% had a height below centile 10 (-1.28 SDS) and 68% had a height below centile 3. Brancati et al [6] reported that the mean stature in 8 adults with clinical KBG syndrome was 149 cm for women and 153.6 cm for men.…”
Section: Literature Review Of Height In Kbg Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Although diagnostic criteria have been proposed by several authors, there is no consensus on the clinical diagnostic criteria for KBG [Skjei et al, 2007;Low et al, 2016;Murray et al, 2017]. Eight major criteria were initially defined (macrodontia of the upper central permanent incisors, characteristic facial appearance, hand anomalies, neurological involvement, delayed bone age, costovertebral anomalies, short stature, and the presence of a first-degree relative with KBG syndrome) [Skjei et al, 2007].…”
mentioning
confidence: 99%
“…shown to cause KBG syndrome (MIM148050), characterized by intellectual disability (ID), behavioral abnormalities, macrodontia of upper central incisors, and skeletal anomalies (Brancati et al 2006;Herrmann et al 1975;Skjei et al 2007;Sirmaci et al 2011). Heterozygous deletions at 16q24.3 that contain the ANKRD11 gene were also described in patients with ID, autistic spectrum disorder, and in some cases with brain anomalies, a clinical phenotype overlapping with KBG syndrome (Marshall et al 2008;Willemsen et al 2010;Handrigan et al 2013;Isrie et al 2012;Sacharow et al 2012;Khalifa et al 2013;Miyatake et al 2013).…”
mentioning
confidence: 99%